1998
DOI: 10.3892/ijmm_00000122
|View full text |Cite
|
Sign up to set email alerts
|

Danazol enhances Fas-mediated apoptosis in human endometrial epithelial cells within normal physiology

Abstract: Abstract. Local danazol therapy reduces the signs and symptoms of endometriosis without inhibition of regular ovulation and menstruation and without atrophic changes to the endometrium or vaginal wall. It has been suggested that danazol has possible non-cytotoxic direct actions on eutopic endometrial cells and endometriotic cells. We have investigated the direct effects of danazol on a human endometrial epithelial cell line, HHUA, which is believed to retain many normal intracellular signaling pathways. A thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Recently, we found that danazol enhances Fas-mediated apoptotic signals within physiological variations (27). The present study has revealed that danazol regulates the functional cellular subpopulation ratios of ESCs by different mechanisms from M-CSF (30).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Recently, we found that danazol enhances Fas-mediated apoptotic signals within physiological variations (27). The present study has revealed that danazol regulates the functional cellular subpopulation ratios of ESCs by different mechanisms from M-CSF (30).…”
Section: Discussionmentioning
confidence: 80%
“…However, in vitro experiments using thoroughly dissolved danazol in 0.5% ethanol revealed that even high concentrations of danazol did not inhibit the proliferation rates of endometrial epithelial cells and ESCs (25). Moreover, we recently reported that danazol enhances Fas-mediated apoptosis within physiological variations (27). In the present study, we examined the effects of danazol on normal human ESCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature data regarding diseases other than CLL show a similar mechanism of action of danazol. Tanaka et al [ 28 ] showed that danazol enhanced Fas-mediated apoptosis in human endometrial epithelial cells, indicating involvement of a receptor cascade. However, another study reported that expression of BCL-2 was decreased in adenomyotic endometrium treated with danazol, which indicated activation of a mitochondrial cascade [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 The underlying mechanism is to be fully elucidated, but Fasmediated apoptosis and inhibition of aromatase gene transcription have been implicated. [33][34][35] The use of oral danazol has been limited by its androgenic side effects, which make compliance difficult and limit prolonged use. Recent interest has focused on alternative, more targeted routes of administration that would limit its systemic androgenic side effects.…”
Section: Vaginal Danazolmentioning
confidence: 99%